2019
DOI: 10.18632/oncotarget.26513
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pituitary adenoma expression patterns suggests a potential role for the NeuroD1 transcription factor in neuroendocrine tumor-targeting therapies

Abstract: NeuroD1’s roles in the pathogenesis of pituitary adenomas and in the biology of the normal adult pituitary gland have been insufficiently researched. Much of the work investigating its expression patterns has yielded contradictory results. Objective: morphological study of NeuroD1 transcription factor expression in different types of pituitary adenomas and in normal adult human pituitary glands. Materials and methods: This study analyzed 48 pituitary adenomas and nine normal pituitary glands. In all cases, imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In conclusion, the new 2017 classification is practical and reasonable from both a molecular and clinical pathology perspective, as this classification is based on IHC studies of transcription factors, which are intuitively understandable and are technically and diagnostically helpful (26). The present study is not the first clinicopathological analysis of pituitary adenomas based on the new classification (26,(47)(48)(49)(50), however previous studies have also showed that the new WHO 2017 classification categorizes less null cell adenomas compared with previous classifications (26,47). In the present study, patients with pituitary tumour diagnosed after 2017 were systematically classified according to the 2017 classification criteria and provides a theoretical basis for the accurate diagnosis of PAs.…”
Section: Group ------------------------------------------------------mentioning
confidence: 80%
“…In conclusion, the new 2017 classification is practical and reasonable from both a molecular and clinical pathology perspective, as this classification is based on IHC studies of transcription factors, which are intuitively understandable and are technically and diagnostically helpful (26). The present study is not the first clinicopathological analysis of pituitary adenomas based on the new classification (26,(47)(48)(49)(50), however previous studies have also showed that the new WHO 2017 classification categorizes less null cell adenomas compared with previous classifications (26,47). In the present study, patients with pituitary tumour diagnosed after 2017 were systematically classified according to the 2017 classification criteria and provides a theoretical basis for the accurate diagnosis of PAs.…”
Section: Group ------------------------------------------------------mentioning
confidence: 80%